Consumption of Dietary Advanced Glycation End Products Promotes Prostate Tumor Growth by Creating a Tumor Enhancing Stromal Microenvironment. (29th May 2020) - Turner, David; Krisanits, Bradley; Frye, Callan; Nogueira, Lourdes; Schuster, Ried; Ford, Marvella; Omonefe, Oomfuma; Steck, Susan; Peterson, Lindsay; Lilly, Michael; Thomas, Courtney; Ahmed, Mahtabuddin; et al.
Abstract: Objectives: The literature regarding the role of advanced glycation end products (AGEs) on tumor biology has shown only moderate promise reflected by increases in cell growth, migration and invasion in vitro which is not supported by increased tumor growth in vivo 14-16 – A caveat to these studies is that they are centered upon a single AGE peptide and a subsequent assessment of their molecular effects on tumor epithelial cells. The objective is to show that by feeding mice a high AGE diet we can recapitulate a microenvironment comprising of a wide spectrum of AGEs which can influence neoplastic growth. Methods: We recapitulated a dietary-AGE induced microenvironment in syngeneic xenograft and spontaneous breast and prostate mouse cancer models and the effects on tumor growth assessed. The mechanistic consequences of dietary-AGEs on the tumor microenvironment were further defined using mouse and human primary and immortalized two-compartment co-culture ex vivo culture models. Results: Dietary-AGE consumption in breast and prostate tumor models significantly accelerated tumor growth by functioning as ligand to the transmembrane receptor for AGE (RAGE). Our studies demonstrate that AGEs promote neoplastic growth by functioning as ligand to RAGE expressed in the tumor stroma not the tumor epithelial cells. Dietary-AGE activation of RAGE in both breast and prostate tumors caused a regulatory program of 'activated fibroblasts' defined by increased expression of cancer associated fibroblast markers, NFkB and MYC upregulation, and pro-tumorigenic paracrine secretion. Complementary to this, our published studies show that high intake of dietary AGE after BCa diagnosis increases risk of mortality in postmenopausal women. Conclusions: These data demonstrate, for the first time, the oncogenic potential of dietary-AGEs in promoting neoplastic growth. This lays the foundation for strategic changes aimed at reducing cancer incidence and mortality as pharmacological, educational and/or interventional strategies aimed at reducing the dietary-AGE accumulation pool may one day be viewed as universal cancer preventative and/or therapeutic initiatives especially when combined with existing therapies. Funding Sources: David P. Turner was supported by grants from the NIH/NCI, R21 CA194469 and U54 CA21096..